The association between medication use and gait in adults with intellectual disabilities. Issue 10 (4th September 2020) - Maas, S.; Festen, D. A. M.; Hilgenkamp, T. I. M.; Oppewal, A.
Abstract: Background: Adults with intellectual disabilities (ID) often have polypharmacy and often use antipsychotics. Both polypharmacy and antipsychotics have a negative effect on gait in the general population, but this has not been studied in adults with ID. These negative effects may add to pre‐existing gait disturbances in adults with ID and increase the risk for adverse health outcomes in this population. Therefore, the aim of this study is to investigate the difference in gait parameters between adults with ID with and without polypharmacy and between adults with ID using and not using antipsychotics. Method: The gait parameters of 31 participants were collected with the GAITRite walkway, a pressure sensitive walkway measuring spatial and temporal gait parameters, in addition to information about personal characteristics, prescribed medication and presence of polypharmacy. Results: After adjustment for sex and body mass index, participants with polypharmacy had a significantly shorter step length [polypharmacy B (SE) = −0.079 (0.034), P = 0.03], shorter stride length [polypharmacy B (SE) = −0.157 (0.069), P = 0.03] and longer double support time [polypharmacy B (SE) = 0.0004 (0.0001), P = 0.047]. Participants using antipsychotics had a significantly longer double support time [antipsychotic use B (SE) = 0.0003 (0.0002), P = 0.019]. Conclusion: This study showed for the first time that both polypharmacy and using antipsychotics are associated with gait in adults with ID. The differences seem to resemble a more cautious gait. Further investigation with larger study samples, additional medication types and dosages are needed to acquire more insight in this important topic.